Development of the Investigator® 26plex QS Kit: A New multiplex PCR Kit for Global STR analysis. Issue 1 (December 2019) - Vraneš, Miroslav; König, Margaretha; Cornelius, Stefan; Kohns, Annika; Elliott, Keith; Prochnow, Anke; Scherer, Mario
Abstract: STR assays for forensic casework must conform to national DNA standards. QIAGEN developed the Investigator 26plex QS Kit as an assay to co-amplify 25 markers, including the current Chinese, CODIS and European standard markers in one reaction. The kit is designed for purified DNA from casework and reference samples. The new Fast Reaction Mix 3.0 ensures not only robust and fast PCR amplification with improved inhibitor resistance and easy handling, but also provides enhanced robustness towards DNA overloading and stability. Highly sensitive, yielding rapid and reliable results from trace DNA, the kit is suitable for all forensic applications and paternity testing. It can also be used for direct amplification of reference samples like blood or buccal cells on FTA cards or swabs. Furthermore, with the inclusion of Penta E and Penta D in the marker set, the Investigator 26plex QS Kit offers very high discriminatory power. The assay uses a 6-dye technology to keep the amplicon length of the markers short and to avoid marker overlap. The kit contains QIAGEN's Quality Sensor System (QS1 and QS2) as an internal PCR control.